Đánh giá đồng đẳng trong quá trình học tập môn học: Nghệ thuật thực hành múa - Lê, Quỳnh Trang (Hiệp hội các Trường Đại học, Cao đẳng Việt Nam, 2023)
Dance is developing day by day, practicing dance not only improves individual performance skills but also cultivates confidence, creativity, and ability to evaluate and critique to apply in the path of dance. professional later. Peer assessment is considered as a part of assessing the learning process, helping learners get better feedback from other members of the class about their knowledge, skills, and attitudes. This study presents a 7-week trial to examine the impact of peer assessment on the development of dance skills among students at Hanoi University of Culture. The results show that: students who are peer-reviewed in this course have a marked improvement in dance skills, and have a higher ability to assess independence and higher academic satisfaction than with students who did not participate in the experiment.